Protocol: an improved method to quantify activation of systemic acquired resistance (SAR) - Rufián Plaza, José Sebastián; Rueda-Blanco, Javier; Beuzón-López, Carmen del Rosario; Ruiz-Albert, Francisco Javier (BMC (Springer Nature), 2019)
Background: Plant responses triggered upon detection of an invading pathogen include the generation of a number of mobile signals that travel to distant tissues and determine an increased resistance in distal, uninfected tissues, a defense response known as systemic acquired resistance (SAR). The more direct means of measuring activation of SAR by a primary local infection is the quantification of pathogen multiplication in distal, systemic sites of secondary infection. However, while such assay provides a biologically relevant quantification of SAR, it is hampered by experimental variation, requiring many repetitions for reliable results. Results: We propose a modification of the SAR assay based on the Arabidopsis-Pseudomonas syringae pathosystem exploiting the knowledge of source-sink relationships (orthostichies), known to centralize SAR-competency to upper leaves in the orthostichy of a lower primary infected leaf. Although many sources of variation such as genotypes of plant and pathogen, inoculation procedure, or environmental conditions are already taken into account to improve the performance of SAR assays, a strict leaf selection based on source-sink relationships is not usually implemented. We show how enacting this latter factor considerably improves data reliability, reducing the number of experimental repetitions for results. Conclusions: Direct selection of leaves for both primary and secondary inoculation exclusively within the orthostichy of the primary infected leaf is a key element on reducing the number of experimental repetitions required for statistically relevant SAR activation results.
Keywords: Pseudomonas syringae; Systemic Acquired Resistance (SAR); Plant Immunity